Meningeal Foam Cells and Ependymal Cells in Axolotl Spinal Cord Regeneration - Enos, Nathaniel; Takenaka, Hidehito; Scott, Sarah; Salfity, Hai V. N.; Kirk, Maia; Egar, Margaret W.; Sarria, Deborah A.; Slayback-Barry, Denise; Belecky-Adams, Teri; Chernoff, Ellen A. G. (Frontiers in Immunology, 2019)
Foam cells (foamy macrophages) and multinucleated giant cells (MNGCs) accumulate on and in invasive fibrotic meninges of transected Axolotl spinal cord (salamander Ambystoma mexicanum). These cells localized closely to regenerating cord ependymal cell (ependymoglial) outgrowth. In situ fluorescent dye labeling showed accumulated cells to be lipid-laden. Actin localization showed characteristic foam cell and MNGC podosome and ruffled border-containing sealing ring structures attaching these cells to reactive meninges in situ and on explant cultures in vitro. Characteristic intermediate filaments surrounded nuclei in electron microscopy studies. Lipid-laden cells were further characterized as foamy macrophages by expression of lipid scavenger receptor CD36, co-transporter toll-like receptor-4 (TLR4) and cysteine proteinase cathepsin K. Foam cells apparently perform a positive role in Axolotl cord lesion sites, serving as a sink for lipid and myelin breakdown products. Foam cell/ependymal cell co-culture supported dispersion of ependymal cell outgrowth known to remodel the spinal cord lesion site. Oxidized low density lipoprotein (Ox-LDL) and myelin fragments from damaged cord, and extracellular matrix (ECM) from the invasive meninges must be removed from the lesion site during regeneration. Control and regenerating cord sections, as well as live or fixed reactive ependymal/meningeal explant cultures, were used to localize CD36 and TLR4, visualize lipids and myelin sequestered in vivo, examine the uptake of DiI-Ox-LDL and DiI-myelin fragments in vitro in foam cells and MNGCs. Reagents included fluorescent actin probes, myelin probes, neutral and polar lipid labels and fluorescently-labeled Ox-LDL and myelin fragments for uptake studies. Competitive inhibitor treatment using Sulfo-N-succinimidyl Oleate verified the role of the lipid scavenger receptor CD36 in lipid uptake. Foam cells and reactive ependymoglia both sequester lipid using CD36/TLR4. Foam cells, smaller MNGCs and ependymal cells took up lipid and myelin fragments in vivo and DiI-myelin in vitro. Only foam cells and smaller MNGCs took up additional Ox-LDL in vitro. Meningeal flat mounts and lesion site cultures were used to identify cathepsin K expression in foam cells, MNGCs and ependymal cells. Comparison of 3H-glucosamine uptake in ependymal cells and foam cells showed that only ependymal cells produce and degrade ECM, while foamy macrophages only removed ECM.